Multimodality Imaging Assessment of Ocular Ischemic Syndrome - Hui Wang; Yanling Wang; Hongyang Li (Journal of Ophthalmology)
Objectives. To assess the underlying mechanisms of OIS and confirm the haemodynamic and retinal structure changes of early OIS. Methods. An observational cross-sectional study was conducted of 60 internal carotid artery (ICA) stenosis patients, and they were divided into OIS and control group. Colour doppler imaging, optical coherence tomography, and fundus fluorescein angiography were performed. Results. The middle cerebral artery (MCA) stenosis differs significantly between the two groups. More OIS patients had new collateral patency of posterior communicating artery (PCoA) and retrograde flow via the ophthalmic artery (OA) (p<0.001). The peak systolic velocity (PSV) in central retinal artery (CRA) and choroidal thickness (CT) was significantly reduced in OIS patients (p=0.001 and p<0.001). The arm-retina time (ART) and the retinal arteriovenous passage time (AVP) were prolonged in OIS patients (p<0.001 and p=0.001). CT, ART, and PSV of the CRA showed high sensitivity, while ART and ICA stenosis grade showed high specificity for the diagnosis of OIS according to ROC curve. Conclusions. Patients who suffered from severe ipsilateral ICA stenosis, new collateral patency of PCoAs, and MCA stenosis may be more susceptible to OIS. The most sensitive sign is PSV of CRA and CT, and the most specific sign is ART.